The Effect of Coordination, Reaction Speed and Kinesthetic Perception on Feilding (High Catch) Skills in Cricket Athletes, West Java Province - Janky Dewi Amar; Johansyah Lubis; Iwan Herawan (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to examine the effect of coordination, reaction speed and kinesthetic perception on fielding skills (high catch) in cricket athletes in West Java province. The research population was all cricket athletes in West Java Province, consisting of the City of Bekasi, which consisted of 14 sons and 14 women, and the City of Bandung, 14 men and 14 women. So the total population is 56 athletes. The sampling technique in this research is total sampling. So the sample in this study was 56 cricket athletes from the province of West Java. The coordination instrument (X1) uses the eye-hand-foot coordination Test. The reaction speed instrument (X2) uses the Ruler drop test. Kinesthetic perception instrument (X3) using the kinesthetic perception test. Fielding (Y) using the Fielding (High catch) test. The results of this study are the direct effect of variable X1 on Y = 55.4%. The direct effect of variable X2 on Y = 3.2%. The direct effect of variable X3 on Y = 6.6%. The direct effect of the X1 variable on X3 = 92.7%. The direct effect of variable X2 on X3 = 2.7%. The indirect effect of variable X1 on Y through X3 = 98.2%. The indirect effect of variable X2 on Y through X3 = 4.9%.